Structural packaging design your own boxes and 3-D forms - Jackson, Paul (London Laurence King, 2012)
Unlike other packaging titles, which simply provide templates to copy, this book enables designers of all packaging types to create 3-D packaging forms that are specific to their needs rather than based on an existing design. Structural Packaging gives the reader an understanding of the underlying principles of packaging construction and the technical knowledge and confidence to develop a greater number of their own unusual and innovative designs.
Keywords: Packaging -- Design